2010
DOI: 10.3109/13561820903520369
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional attitudes and perceptions: Results from a longitudinal controlled trial of pre-registration health and social care students in Scotland

Abstract: This study made use of a controlled longitudinal design to assess the impact on pre-registration health and social care students of an interprofessional intervention on the attitudes to and perceptions of interprofessional ideals. Evaluation, over four years, of Nursing, Occupational Therapy, Podiatry, Prosthetics and Orthotics, Physiotherapy and Radiography students was performed using the adapted versions of the Readiness for Interprofessional Learning Scale (RIPLS) and the Interdisciplinary Education Percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 26 publications
8
82
2
4
Order By: Relevance
“…Although whereas as Pollard et al (2006) reported that female students were comparatively positive about IPE in their longitudinal study of undergraduate students attitudes, other studies reported that gender did not have any noticeable effect on the delivery of IPE (Bradley et al 2009;McFadyen et al 2010). In their later study, Pollard & Miers (2008) found that there were no significant differences in scale scores on the basis of gender.…”
Section: Learner Characteristicsmentioning
confidence: 78%
See 3 more Smart Citations
“…Although whereas as Pollard et al (2006) reported that female students were comparatively positive about IPE in their longitudinal study of undergraduate students attitudes, other studies reported that gender did not have any noticeable effect on the delivery of IPE (Bradley et al 2009;McFadyen et al 2010). In their later study, Pollard & Miers (2008) found that there were no significant differences in scale scores on the basis of gender.…”
Section: Learner Characteristicsmentioning
confidence: 78%
“…In contrast, a small number of studies gathered data over a longer period. For example, Pollard et al (2006), Pollard & Miers (2008) and McFadyen et al (2010) collected data over a fouryear period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to McFayden et al, Wakely, Brown, and Burrows (2013) found significant positive changes for three of the sub-scales (teamwork and collaboration, positive identity and negative identity) but no change for the roles and responsibilities sub-scale. Student participation in both these IPL studies was mandatory, however one took place in the clinical setting ( Wakely, Brown, and Burrows 2013) whereas the other was classroom-based (McFadyen et al 2010). Differences in context may therefore influence the effect of an educational intervention on RIPLS.…”
Section: Discussionmentioning
confidence: 99%